2020
DOI: 10.1080/09720510.2020.1833448
|View full text |Cite
|
Sign up to set email alerts
|

Impact of counseling on psychological health during lockdown of Covid-19

Abstract: Covid-19 is one of the biggest issues of the world. It is an untreatable and communicable disease. Therefore lots of countries are in a lockdown process. Our government has also announced lockdown since mid of March 2020. During this pandemic people are feeling psychological presser like anxiety, depression and stress because they are not able to come out their homes and are not in a position to fulfill their needs. In this situation central and state government has launched various types of counseling program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The pandemic has left a psychic scar that still needs tending. With psychological pressures like depression, anxiety, and stress that then may manifest into health issues like insomnia and substance abuse, counseling is necessary to be able to support those who are affected [122]. Due to the social and physical distancing required by the COVID-19 pandemic, the usual means of support are no longer as accessible and have been disrupted immensely [123].…”
Section: Counselingmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic has left a psychic scar that still needs tending. With psychological pressures like depression, anxiety, and stress that then may manifest into health issues like insomnia and substance abuse, counseling is necessary to be able to support those who are affected [122]. Due to the social and physical distancing required by the COVID-19 pandemic, the usual means of support are no longer as accessible and have been disrupted immensely [123].…”
Section: Counselingmentioning
confidence: 99%
“…In response, countries have begun to adopt electronic mental health tools and, while the acceptance of these tools was quite minimal before the pandemic, they have now become the best and highest-quality solutions available given the circumstances brought about by the need for physical distancing [124,125]. As for how effective counseling during the pandemic is, research has shown that individuals who regularly attend counseling sessions experience lower levels of depression, anxiety, and stress [122].…”
Section: Counselingmentioning
confidence: 99%
“…Furthermore, social isolation measures and loneliness have shown to increase the risk of depression up to 9 years later. The duration rather than intensity of loneliness and the presence of previous mental health disorders are strong risk factors for these mental health symptoms [ 9 , 13 - 16 ].…”
Section: Effect Of the Pandemic On Young Adultsmentioning
confidence: 99%
“…With social distancing measures in place, digital solutions have provided new ways of medical care services and support. Online therapy sessions or “cyber-counselling” has become a reasonable counselling conveyance strategy during this pandemic [ 16 , 18 , 20 , 21 ]. An irrefutable advantage of online counselling is that of availability and reach.…”
Section: Recommendationsmentioning
confidence: 99%
“…Other researchers have suggested how policies that encourage self-learning and participation in diversified social activities can be devised to ensure healthy ageing among the elderly (Hung and Lu 2013;Zeng 2013). Some researchers have emphasised that counselling can positively contribute to psychological health during the lockdown (Kumari and Singh 2020;Budimir et al 2021). Healthy, psychological ageing consists of three aspects: evaluative wellbeing (life satisfaction), hedonic wellbeing (feelings of happiness, etc.…”
Section: Healthy/active Ageing: Psychological Spiritual and Social Dimensionsmentioning
confidence: 99%